Systematic Thermodynamics of Hydration (and of Solvation) of Inorganic Solids - Glasser, Leslie; Jones, Franca (American Chemical Society, 2009)
The thermodynamics of the formation of solid and liquid inorganic hydrates and ammoniates is examined. In earlier studies, average values of the Gibbs energy of reaction, ?rG, assuming a constant additivity per mole of bound water, have been obtained and have suggested that hydration is always marginally thermodynamically favourable. More detailed consideration now demonstrates that the mean value of ?rG per mole of water, from anhydrous parent to hydrate within a sequence, increases consistently towards zero, becoming progressively less favourable as the degree of hydration, n, increases, and broadly independent of any structural features of the materials. Furthermore, the consistent behaviour suggests that missing intermediate hydrates in hydrate sequences are likely to be thermodynamically stable, even if difficult to prepare, isolate or measure.The behaviour of ammoniates is similar but less regular, the irregularity being ascribed to stronger interactions within the solid ammoniates than in the hydrates. The ?Ostwald Rule of Stages? suggests that the first precipitate from a supersaturated solution is usually a metastable phase, having an intermediate value of the Gibbs energy between that of the anhydrous parent and of the thermodynamically stable phase, then progressing to the stable phase with the lowest Gibbs energy - implying kinetic rather than thermodynamic control of the sequence of precipitation. The implications for hydrate formation are briefly considered.